2005
DOI: 10.1256/qj.04.63
|View full text |Cite
|
Sign up to set email alerts
|

Summer mistral at the exit of the Rhône valley

Abstract: SUMMARYThe paper examines the three-dimensional structure and dynamics of the mistral at the Rhône valley exit on 28 June 2001. The mistral refers to a severe wind that develops along the Rhône valley in southern France. This summer mistral event was documented in the framework of the ESCOMPTE field experiment. The dynamical processes driving the circulation of the mistral in the Rhône valley and particularly wake formation and planetary boundary layer (PBL) inhomogeneity at the scale of Rhône valley delta are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 44 publications
1
51
0
1
Order By: Relevance
“…In the central Mediterranean, the north-north-west cold and dry mistral (e.g. Jansá 1987;Jiang et al, 2003;Caccia et al, 2004;Corsmeier et al, 2005;Drobinski et al, 2005;Guénard et al, 2005Guénard et al, , 2006Lebeaupin Brossier and Drobinski, 2009) and its companion wind the tramontane (e.g. Drobinski et al, 2001) blows in the Gulf of Lion, occasionally up to the African coasts (Salameh et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the central Mediterranean, the north-north-west cold and dry mistral (e.g. Jansá 1987;Jiang et al, 2003;Caccia et al, 2004;Corsmeier et al, 2005;Drobinski et al, 2005;Guénard et al, 2005Guénard et al, , 2006Lebeaupin Brossier and Drobinski, 2009) and its companion wind the tramontane (e.g. Drobinski et al, 2001) blows in the Gulf of Lion, occasionally up to the African coasts (Salameh et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…As for the mean surface wind field and wind variability, the PV field is very sensitive to the nudging time. The major source of PV, present in all simulations, is the mistral (generating positive PV)/tramontane (generating negative PV) winds, shooting through the Rhône and Aude valley gaps between the Alps and the Pyrenees, and bounded on both sides by mountain-induced PV banners shed from major peaks in the Pyrenees, the Massif Central and the Alps Drobinski et al, 2005). When τ increases, smaller-scale PV features appear in the western basin in the lee of Corsica-Sardinia (positive PV) and at the exit of the Ebro valley (Spain) where the cierzo blows.…”
Section: Discussionmentioning
confidence: 99%
“…Alpert et al 1995;Trigo et al 1999), topographically-induced strong winds like Mistral (e.g. Drobinski et al 2005;Guénard et al 2005Guénard et al , 2006Corsmeier et al 2005) and Tramontane (e.g. Drobinski et al 2001), which are companion winds blowing south from the French Mediterranean coast to the African coasts (Salameh et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of occurrence and intensity of Mistral and Tramontane winds are of great interest not only for risk assessments under changing climatic conditions, but also for scientific reasons. Many case studies have dealt with Mistral and Tramontane events (e.g., Drobinski et al 2005;Berthou et al 2016). Obermann et al (2016) found the sea-level pressure fields associated with Abstract The characteristics of the mesoscale Mistral and Tramontane winds under changing climate conditions are of great interest for risk assessments.…”
Section: Introductionmentioning
confidence: 99%